Hybrid renewable energy systems sizing for the colombian context by multiple attribute decision making evaluation - Marenco-Porto, Carlos Andres; Torres-Madroñero, José Luis; Nieto-Londoño, César; Arenas-Castiblanco, Erika; Zapata-Benabithe, Zulamita; Vidal Gutierrez, Humberto Ricardo (My University, 2023)
Due to the environment's adverse effects caused by electricity generation based on fossil resources, renewable energies have been promoted, where wind and solar energy stand out for the recent reduction in installation, operation, and maintenance costs. Wind and solar are stochastic natural resources; however, their complementarity is exploited by Hybrid Renewable Energy Systems, impacting energy availability for a particular demand. This study presents the sizing of hybrid renewable systems considering the resources existing in La Guajira, Colombia, applying an Analytic Hierarchy Process to evaluate the Loss Power Supply Probability, the Total Annual Cost and the Levelized Cost of Energy, and the Net Present Value of all possible configurations. Furthermore, the results were compared with a previous study that optimized the configurations through Genetic Algorithms and Particle Swarm Optimization. Three demand profiles were analyzed: (1) a reference case that includes a characteristic normalized non-interconnected single-family house composed of three users with an electrical consumption of 3.6 kWh/day, (2) the previous reference case plus the energy consumption for a water purifying system of 200 L/user/day, aiming a load of 4.3 kWh/day, and (3) a load profile for 150 users non-interconnected community with a demand of 156.2 kWh/day. Based on the results, it is observed that a 100% solar photovoltaic system presented the lower economic indicators values without affecting the availability of electricity generation for the cases with a minimum energy load (i.e., cases (1) and (2)). However, with the energy demand increasing, hybridization with wind turbines is essential to meet the load during operation.